The New Audiovisual Communicators: Career Opportunities and Required Professional Training in Spain Context - Grijalba de la Calle, Nicolás (2022)
The digital transformation of the audiovisual environment and its effects on the logic of creation, production and marketing of the communication industries has led to the emergence of new professional profiles in audiovisual communication studies in Spain. Specialists in this field identify three scenarios of professional specialization that universities should attend to in the training of future audiovisual professionals: (a) design, programming and development of applications and software; (b) digital marketing and management of video and audio platforms for online use; and(c) visual effects, virtual scenography and design of 3D characters and atmospheres. This study aims to identify the skills and abilities associated with each of these profiles by combining scientific literature, reports and studies with in-depth interviews with renowned professionals and professors.